JOBLESS GROWTH DI KOTA MAGELANG TAHUN 2016: PENYEBAB DAN SOLUSINYA DI MASA MENDATANG - Yulius Pratomo (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2021)
This research aims to determine the causes of jobless growth in Magelang Municipality in 2016 and provide solutions if the same problem occurs in the future. This research was conducted in an exploratory manner using qualitative analysis techniques. The data needed in this study were obtained from the results of FGDs with related agencies in Magelang Municipality and from the results of literature searches on the internet. The results showed that jobless growth in Magelang Municipality tends to be caused by economic growth in Magelang Municipality which is biased towards certain sectors. Investment spending made in certain sectors has not been able to provide a multiplier effect to create new jobs, as well as increase output and income in other business fields in Magelang Municipality. The solution to the problem of jobless growth, for example, the Magelang Municipality Government and stakeholders need to develop a city business development plan that is complementary between business fields.